Educação contextualizada para a convivência com o Semiárido em Ipaporanga-CE - Pessoa, Francisco Eder de Sousa (2023)
This academic work analyzes how the Context Education for the semi-arid living experience is becoming an education policy in the Ipaporanga municipality, in the Ceará State, taking into consideration the context education practices strengthening between 2013 and 2021, taking as references the discussions about this educational proposal. It seeks to make a reflection about the implementation process of this proposal in the Ipaporanga municipality as of a macro vision, taking into account the historical process in the Brazilian semiarid. The education given to the semiarid people, guided by the traditional practices, became an instrument of reproduction of the negative collective opinion about the semiarid, as a miserable place, disregarding its potentials and peoples knowledge. From the 80's, a movement started, contesting the at the time education given to the semiarid people. That way, appears the discussion and defense of a context education to the semiarid living, turning into an important ally of the developing the perspective of the semiarid living, instead of drought combat. In this research, It was used the qualitative research as the investigation method, considering it adequate for educational researches, as it seeks the understanding of a particular phenomenon, whether It is social or educational or even the reality transformation. That way, it were made semi-structural interviews with school managers, teachers, teachers-trainers, representatives of the Brazilian Semiarid Education Network (RESAB), Crateús Diocesan Caritas and Pastoral Agent from the Ipaporanga Parish. These subjects are directly engaged in the implementation of this policy in the semiarid region, more specifically, in the Ipaporanga municipality. Freire's pedagogy and its contributions from the Popular Education, as well the perspective of the "thick description" from the Clifford Geertz anthropology and the complex thought from Edgard Morin are part of the theoretical background used on this research. The results show that the understanding about the context education for the semiarid living is still something restricted to the School space and a severe deepening in the pedagogical extent, lacking a more punctual recovery over the others extents of this educational proposal, specially the political extent, considering it as the reality transforming aspect. The analysis points out the need of a full application of the Municipal Law n° 353, from 2015, which is about the context education directives and field education in Ipaporanga. It is still necessary the development of the proposed curricular policy of the municipality, an important and necessary document to the affirmation of this proposal as a public educational policy. In the end, It is possible to state that the contextual teaching methodology, active in the education context proposal, efficiently contributed to improve the Ipaporanga municipality teachers' pedagogical practices